The Effect Of Giving Supremo Made From Active Glyphosate On The Control Of Banyan Weeds On Oil Palm Plants Produces Using The Root Infusion System - Zulfan Ilham; Harahap FS; Badrul Ainy Dalimunthe; Dini Hariyati Adam (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The internship activity at PT Supra Matra Abadi Kebun Aek Nabara (KAN) in Bilah Hulu District, LabuhanBatu Regency, North Sumatra Province, this activity was carried out for four months, March-July and the method used was a completely randomized design (CRD) with 2 different treatments, namely by concentration of 6% and 7%. Results: Afdilling III PT Supra Matra Abadi controlled banyan weeds using two treatments, namely manually and chemically. The banyan weed is a nuisance plant, because its life clings to or suffocates the oil palm plant. The negative impacts on oil palm plants are pest attacks, competition occurs, humidity increases, making it difficult for the pruning and harvesting processes. The banyan weed population in PT Supra Matra Abadi is in block C87C and block C87G. The purpose of this study was to determine the effective and efficient concentration in the use of the supremo herbicide with the active ingredient glyphosate. Based on the results of research that has been carried out from the two concentrations of the herbicide supremo 480 SL which is effective and efficient for controlling banyan weeds in oil palm plants, namely a concentration of 7%. Because at a concentration of 6% it takes 30 days to see the banyan weed die